Interprofessional teaching rounds in medical education: improving clinical problem-solving ability and interprofessional collaboration skills - Peiwen Yang; Ting Xiong; Xiyuan Dong; Shulin Yang; Jing Yue (Medical Education Online)
Interprofessional teaching rounds are a practical application of interprofessional education in bedside teaching, yet there is a lack of research on how interprofessional teaching rounds should be implemented into medical education. This study aimed to describe our experience in developing and implementing interprofessional teaching rounds during a clerkship rotation for medical students, and compares its strengths and weaknesses relative to traditional teaching rounds. Medical students were assigned to either the interprofessional teaching round group (n = 24) or the traditional teaching round group (n = 25), and each group participated in their assigned type of teaching round. A quiz including medical knowledge of gynecological and obstetric diseases was used to assess the students’ diagnostic and treatment abilities after teaching rounds. Additionally, a survey was conducted among students to evaluate whether the interprofessional teaching rounds were helpful. The results showed that when using interprofessional teaching rounds, the test score for medical knowledge related to the diagnosis and treatment of gynecological and obstetric diseases was significantly higher than the traditional teaching round group (85.5 ± 11.2 vs 78.3 ± 12.5, p = 0.038). Additionally, the interprofessional teaching rounds significantly enhanced understanding of clinical application, identification, and appropriate problem-solving in cases, as well as examination of different disciplinary aspects of a case, and improvement of interdisciplinary collaboration skills compared to traditional teaching rounds. Our study demonstrates that interprofessional teaching rounds can serve as an effective teaching method for enhancing medical students’ ability to collaborate interprofessionally and to solve clinical problems comprehensively.